Implementasi Kepemimpinan Transformasional Dalam Pendidikan Islam - Robi’ul Afif Nurul ‘Aini (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2019)
The purpose of this paper is to describe the background of the birth of transformational leadership, its development and its implementation in the Islamic education institution. Discussing the research conducted by several people to look for a new paradigm of ideal leadership behavior after feeling some of the unsatisfactory leadership behaviors. The new paradigm is transformational leadership. The method used to achieve the objectives of writing is literature study. General conclusions show that transformational leadership behavior arises and is recognized as the most ideal leadership theory to date,when compared to the transactional leadership theory and situational leadership that existed before. Transformational leadership includes 4 i, namely Idealized Influence, Inspirational Motivation, Intellectual Stimulation, Individual Consideration.